2019
DOI: 10.3390/nu11102450
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Typical Korean Versus American-Style Diets on Gut Microbial Composition and Metabolic Profile in Healthy Overweight Koreans: A Randomized Crossover Trial

Abstract: The Westernized diet has been associated with the pathogenesis of metabolic diseases, whereas a Korean diet has been reported to exert beneficial effects on health in several studies. However, the effects of Western and Korean diets on the gut microbiome and host metabolome are unclear. To examine the diet-specific effects on microbiome and metabolome, we conducted a randomized crossover clinical trial of typical Korean diet (TKD), typical American diet (TAD), and recommended American diet (RAD). The trial inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 97 publications
1
46
0
1
Order By: Relevance
“…A characteristic feature of the Korean diet is that it consumes a lot of fermented foods, including kimchi, a traditional Korean fermented vegetable dish [ 75 ]. It has potential probiotic effects such as cholesterol reduction, antioxidant properties, and antimicrobial activity [ 76 ]. Most of the participants in our questionnaire were on a vegetable-based diet, including kimchi, and participants were instructed to maintain their usual diet for the entire study period.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic feature of the Korean diet is that it consumes a lot of fermented foods, including kimchi, a traditional Korean fermented vegetable dish [ 75 ]. It has potential probiotic effects such as cholesterol reduction, antioxidant properties, and antimicrobial activity [ 76 ]. Most of the participants in our questionnaire were on a vegetable-based diet, including kimchi, and participants were instructed to maintain their usual diet for the entire study period.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found differences in the baseline microbiome of responders versus nonresponders to different diet interventions. Additionally, individuals with differing bacterial gene richness appear to have differing baseline gut microbiota communities that respond distinctively to a given dietary intervention which will influence the diversity of the gut microbe-derived specialized metabolites and circulating metabolites [127][128][129][130][131][132][133][134][135][136].…”
Section: Gut Microbiome/absorptionmentioning
confidence: 99%
“…Ultimately, the K-diet is low in calories and fat, especially animal fat, but high in low glycemic index carbohydrates and vegetable protein. Due to its unique characteristics, the positive influence of the K-diet on metabolic disorders and cardiovascular disease risk has been widely investigated [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous cohort studies and clinical trials on the K-diet have been conducted using various anthropometric markers such as body weight and body mass index as well as blood markers such as total cholesterol, high density lipoprotein (HDL)-cholesterol, low density lipoprotein (LDL)-cholesterol, triglyceride, and fasting blood glucose [ 2 , 3 , 4 , 5 , 6 ]. However, studies investigating the molecular mechanisms by which the K-diet promotes positive health effects are rare, especially those based on microRNAs (miRs) as endpoints.…”
Section: Introductionmentioning
confidence: 99%